Review Essay: Changes in the Attribution of Values to Northern and Arctic Spaces - Elzinga, Aant (Journal of Northern Studies, 2015)
Review of: Silje Gaupseth, Marie-Theres Feerhofer & Per Pippin Aspaas (eds.), Travels in the North, Hannover: Wehrhahn Verlag 2013, Troll Band 13, Tromsø Studien zur Kulturwissenschaft, ISBN 9783865253347, 230 pp.; John McCannon, A History of the Arctic. Nature, Exploration and Exploitation, London: Reaktion Books Ltd. 2012, ISBN 9781780230184, 349 pp.; Martin Breum, Når isen forsvinder. Danmark som stormagt i Arktis, Grønlands rigdomme og kampen om Nordpolen, København: Gyldendal 2013, ISBN 9788702138023, 316 pp.; Barry Scott Zellen (ed.), The Fast-Changing Arctic. Rethinking Arctic Security for a Warmer World, Calgary: University of Calgary Press 2013, ISSN 1701-0004; co-published by the Arctic Institue of America, ISBN 97815523-6460, 395 pp.; Miyase Christensen, Annika E. Nilsson & Nina Wombs, Media and the Politics of Arctic Climate Change. When the Ice Breaks, Houndmills, Basingstoke, Hampshire UK: Palgrave Macmillan 2013, ISBN 9781137266224, 182 pp.